Metode Pembelajaran Tafsir di Sekolah Berbasis ‘Ulum Al-Qur'an - Agus Imam Kharomen (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2020)
[TAFSEER LEARNING METHODS IN 'ULUM AL-QUR'AN BASED SCHOOL]. This paper is aimed to respond to the lack of formulation of tafsir learning methods at schools. This study shows that the learning method with the basis of Ulum al-Qur’an consists of three aspects, i.e. the foundation, learning material, and method. The foundation of tafsir learning comprises three elements; it must be based on the function of the Qur'an, gradual, and not burdensome. Then, the learning materials of tafsir can use the stories contained in the Qur'an, asbab al-nuzul (reason of revelation), and the main themes of the Qur'an. Meanwhile, the tafsir learning process uses the ijmali method. This is a library based study with data sources from books, especially ‘Ulum al-Qur'an Mabahits fi 'Ulum al-Qur'an by Manna' al-Qathan, 'Ulum al-Qur'an by Nuruddin' Itr, Kaidah Tafsir by M. Quraish Shihab, and Membumikan Ulumul Qur’an by Ahsin Sakho Muhammad as well as research results in the form of journals and others in the field of education. In the process, this study uses a descriptive-analytical method with a content analysis approach and contextual interpretation.